A Profile of Border Protection in Egypt : An Effective Rate of Protection Approach Adjusting for Energy Subsidies - Valdes, Alberto; Foster, William (2012)
This study examines recent effective rates of protection across the Egyptian economy, using an ad valorem price wedge introduced by nontariff barriers and energy subsidies, and compares today's effective rates of protection with those of a decade ago. The study uses 23 aggregated sectors from input-output matrix information. Although trade liberalization since the late-1990s has had a considerable impact in reducing protection of some industries, some sectors, such as the food and tobacco sector, remain relatively highly protected, due to tariff escalation and nontariff barriers, and due to energy subsidies. Energy subsidies are not formally sector specific but do favor sectors that are energy intensive (of particular note is the electricity sector). It appears that energy pricing is part of a strategy to subsidize and promote certain industries and in effect offset the dis-protection or taxation that results from tariffs on intermediate inputs. The case of the cement sector is notable because energy subsidies appear to almost exactly offset the negative impacts of tariffs and indirect taxes. The fertilizer sector has zero nominal tariffs, benefiting agriculture, and so a negative effective rate of protection due simply to tariffs on intermediate inputs. However, the fertilizer sector ends up with a very high a positive total effective rate of protection due to energy subsidies.